WLE/Bioversity influenced the Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services (IPBES) to focus on critical interdependencies of biodiverse ecosystems and food production - CGIAR Research Program on Water, Land and Ecosystems (2019)
Building on its scientific work, WLE influenced the Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services (IPBES) to focus on the critical interdependencies of biodiverse ecosystems and food production. The 134 IPBES countries have adopted WLE's proposal to focus its Nexus Assessment on Biodiversity, Food, Health and Water. It will identify nature-based solutions integrating agriculture and biodiversity to support both human health and environmental sustainability. WLE is positioned as a principal contributor to agricultural policy developments in the next decade.